2014
DOI: 10.1038/ejhg.2014.219
|View full text |Cite
|
Sign up to set email alerts
|

C6ORF97-ESR1 breast cancer susceptibility locus: influence on progression and survival in breast cancer patients

Abstract: Genome-wide association studies have identified a single-nucleotide polymorphism (SNP) to be associated with an increased risk of breast cancer. The biology of one of the susceptibility locus C6ORF-ESR1 and whether it also contributes to progression of established disease has not yet been ascertained. We examined the association of rs2046210 and its six linkage disequilibrium SNPs with clinicopathological characteristics, prognosis, and gene expression levels of ESR1 and the C6ORFs (C6ORF97:CCDC170, C6ORF211, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…However, a recent study reported that CLPTM1L is a commonly overexpressed anti-apoptotic factor in lung cancer [30,32]. Our study and previous research suggest that one SNP can be associated with two or more cancers; for example, rs401681 is associated with many cancers including pancreatic cancer, lung cancer, bladder cancer, and hepatocellular carcinoma [33][34][35]. Further studies are needed to clarify the genetic mechanism of esophageal carcinogenesis by fine mapping the susceptibility region of the variants.…”
Section: Discussionmentioning
confidence: 56%
“…However, a recent study reported that CLPTM1L is a commonly overexpressed anti-apoptotic factor in lung cancer [30,32]. Our study and previous research suggest that one SNP can be associated with two or more cancers; for example, rs401681 is associated with many cancers including pancreatic cancer, lung cancer, bladder cancer, and hepatocellular carcinoma [33][34][35]. Further studies are needed to clarify the genetic mechanism of esophageal carcinogenesis by fine mapping the susceptibility region of the variants.…”
Section: Discussionmentioning
confidence: 56%
“…Nothing is known about the function of CCDC170 (coiled-coil domain–containing protein 170), but recurrent ESR1 - CCDC170 rearrangements have been characterized in an aggressive subset of ER + breast cancers 35 . A recent study also showed that higher CCDC170 expression correlated with ER negativity, highly proliferative features and worse clinical outcomes 36 . There are some data to suggest that these genes may cooperatively contribute to the increased proliferative capacity of ER + tumors 20 , and it is tempting to speculate that these may be additional target genes for the candidate causal variants at a subset of the five signals identified here and perhaps responsible for their differential phenotype associations.…”
Section: Discussionmentioning
confidence: 96%
“…Associations between CCDC170 polymorphisms and BC susceptibility, progression, and survival have been reported 25,26,4850. In addition, ESR1 – CCDC170 chromosomal rearrangements have been associated with more aggressive estrogen receptor-positive BCs 51.…”
Section: Discussionmentioning
confidence: 99%